2005
DOI: 10.1177/000313480507100907
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Lymph Node Metastasis on Survival in Patients with Well-Differentiated Thyroid Cancer

Abstract: Though survival for well-differentiated thyroid cancer is very good, specific populations suffer greater recurrence and mortality. Defining these cohorts can significantly influence prognosis and extent of treatment. This study, using a large, multi-institutional database, seeks to determine how the presence of lymph node disease in patients with well-differentiated thyroid cancer affects outcome. The Surveillance, Epidemiology, and End Results (SEER) database is a large-scale sample of 14 per cent of the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
194
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(200 citation statements)
references
References 12 publications
2
194
0
4
Order By: Relevance
“…In fact, lymph node status has been omitted from prognostic schemes which include age, distant metastases, extent of disease, and size (AMES), patient age, tumor grade, tumor extent, and tumor size (AGES), and metastases, patient age, completeness of resection, local invasion, and tumor size (MACIS) . Although, 2 recent Surveillance, Epidemiology, and End Results database reports suggest that nodal disease is in fact a determinant of tumor‐related survival in patients over 45 years of age, clearly the bulk of prognostic importance for PTC nodes centers on recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lymph node status has been omitted from prognostic schemes which include age, distant metastases, extent of disease, and size (AMES), patient age, tumor grade, tumor extent, and tumor size (AGES), and metastases, patient age, completeness of resection, local invasion, and tumor size (MACIS) . Although, 2 recent Surveillance, Epidemiology, and End Results database reports suggest that nodal disease is in fact a determinant of tumor‐related survival in patients over 45 years of age, clearly the bulk of prognostic importance for PTC nodes centers on recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, lymph node involvement in PTC was not included in any of the prognostic staging systems as it was not considered to influence survival. However, it is known from current data that central node metastases, the number of lymph node metastases and locoregional recurrence are all adverse prognostic factors in thyroid cancer 10,11,14,15,17–19,35–37 . Similarly, it is known that central and lateral lymph node metastases are associated with higher rates of recurrence 9,10,12,13,16,20,36,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these low mortality rates, nodal recurrence occurs in up to 20% of patients at 10 years and 30% of patients at 30 years . Some studies have suggested that patients with involved lateral neck lymph nodes at the time of diagnosis have lower rates of disease‐free survival and higher rates of lateral neck nodal recurrence . However, the prognostic influence of nodal metastases in PTC remains controversial …”
Section: Introductionmentioning
confidence: 99%
“…A number of large studies have investigated the impact of lymph node metastases on outcome in patients with PTC . The majority of these studies have suggested that the presence of nodal metastasis is associated with inferior disease‐free survival; however, one of these studies found that the presence of nodal metastases conferred a negative prognostic impact only in patients aged >45 years .…”
Section: Introductionmentioning
confidence: 99%